Co-catalyzed mild and chemoselective reduction of phenyl esters with NaBH(4): a practical synthesis of (R)-tolterodine - Jagdale, Arun R.; Sudalai, Arumugam (Tetrahedron Letters, 2008)
CoCl(2) catalyzes effectively the chemoselective reduction of phenyl carboxylic esters to the corresponding saturated alcohols in high yields using NaBH(4) at ambient conditions. By employing this methodology, the synthesis of (R)-tolterodine, a muscarinic receptor antagonist, has been achieved in high yield and optical purity. (C) 2008 Elsevier Ltd. All rights reserved.